U.S.-Australia Cooperation in the Indo-Pacific Region Through the IPEF Framework in Realizing the Clean Economy Pillar - Bagas Candra Setiawan; Triesanto Romulo Simanjuntak; Novriest Umbu W. Nau (Jurnal Ilmiah Multidisiplin, 2025)
This research focuses on analyzing the cooperation between the United States and Australia within the framework of the Indo-Pacific Economic Framework (IPEF), particularly in realizing the clean economy pillar. Grounded in the Theory of Neoliberalism and the Concept of International Cooperation, this study aims to further examine the dynamics of IPEF collaboration, especially in the context of bilateral relations between the United States and Australia, to enhance economic growth through commodity exports and the development of low-carbon clean technologies to ensure environmental security and sustainability in the face of industrialization. In implementing the clean economy pillar of IPEF, the involvement of Non-State Actors in the energy sector, particularly Chevron Corporation, plays a crucial role in supporting and maximizing Australia’s agenda to become an energy superpower while maintaining environmental safety as a priority. Chevron’s presence is significant in the IPEF cooperation between the United States and Australia due to its substantial impact on the domestic economy and its tangible commitment to carbon emission reduction. This research reveals the importance of bilateral cooperation, investment, and the development of clean technologies in achieving the clean economy pillar of the IPEF.